Pemberdayaan Ibu Rumah Tangga dan Kader Posyandu Melalui Pelatihan Pangan Lokal Berbasis Ikan di Wilayah Kerja Puskesmas Manutapen Kota Kupang - Meirina S. Loaloka; Asweros Umbu Zogara; Agung Ayu Mirah Adi (BADAN PENERBIT STIEPARI PRESS, 2026)
Nutritional problems remain a major public health issue in Kupang City, particularly in the working area of the Manutapen Public Health Center. The low level of community knowledge, especially among housewives and Posyandu cadres, regarding the processing of nutritious local food is one of the main factors contributing to the high prevalence of stunting and undernutrition among children. Meanwhile, the coastal area of Kupang has abundant fish resources that are available throughout the year. However, the utilization of fish as a local food ingredient remains limited to simple traditional preparations such as frying or boiling, which have not yet optimized its nutritional and economic potential. This community service activity was carried out to enhance the capacity and self-reliance of the community through the empowerment of housewives and Posyandu cadres. The training activities included education on balanced nutrition, cooking demonstrations, and hands-on practice in preparing various fish-based products such as nuggets, meatballs, and shredded fish. The results showed a significant improvement in participants’ knowledge, skills, and motivation to use fish as a nutritious, healthy, and economically valuable local food source. Furthermore, many participants expressed interest in developing fish-based products as home-based businesses, which could potentially increase household income and strengthen local food security in the community.